2017
DOI: 10.1620/tjem.243.27
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among Individuals Whose Partners Have Cancer

Abstract: Cancer diagnosis influences both patients and their closest relatives. This cross-sectional study examined psychological distress among individuals whose partners had cancer in a population-based sample. Participants in the survey were citizens residing in Ohsaki City, Miyagi, Japan. Spouse pairs were identified by information of participants' relationship to the householder and address provided by municipality, and we collected self-report information on cancer history and current pain (but not the cause of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Enhancing the Integrated Community Care system may be useful for reducing the caregiving burden. Further, in previous studies, it has been reported that spouses and families of cancer patients were at high risk of mental and/or physical diseases [1][2][3][4][5][6][7][8][9][10]29]. In addition, in this current study, it was found that earlier mortality from a spouse's cancer diagnosis was high.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Enhancing the Integrated Community Care system may be useful for reducing the caregiving burden. Further, in previous studies, it has been reported that spouses and families of cancer patients were at high risk of mental and/or physical diseases [1][2][3][4][5][6][7][8][9][10]29]. In addition, in this current study, it was found that earlier mortality from a spouse's cancer diagnosis was high.…”
Section: Discussionsupporting
confidence: 58%
“…Spouses of cancer patients may experience serious psychological problems, such as psychological distress and depression, after their partner's diagnosis [1][2][3][4][5][6][7]. Their spouse's cancer may also be associated with their own subsequent poor physical well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For young and middle-aged breast cancer survivors, the male spouse is usually the main family caregiver. Nakaya et al [9] reported that when women suffer from malignant tumors, their spousal caregivers face a higher risk of psychological distress and bear a greater caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…In China, For female BC patients, spouses are their main caregivers. Some studies have noted that when a married woman is diagnosed with a malignant tumor, her spouse is at higher risk of psychological distress ( 3 ). As co-sufferers and the most important supporters of BC patients, spouses may experience emotional disorders, stress, and impaired physiological functions which further aggravate the burden of care, ultimately adversely affecting patients’ treatment and quality of life and even causing marital crisis ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%